Performance Metrics for Street and Park Trees in Urban Forests. Issue 6 (17th September 2018) - North, Eric A; D'Amato, Anthony W; Russell, Matthew B
Abstract: Tree performance in urban forests is difficult to evaluate, because there is not a unified metric such as wood volume to determine the highest performers. This study evaluated tree performance metrics for street and park trees in Minneapolis and Saint Paul, Minnesota. Metrics included: diameter at breast height (dbh), canopy projection area (CPA), a growth rate ratio (BRATIO), and a tree performance index (TPI). The BRATIO and TPI incorporated size and growth rate and were developed as quantitative metrics for evaluation of urban trees. Increased pervious surface area under the canopy had a positive influence on all metrics investigated. Metric comparisons showed larger mean dbh and CPA for street trees and higher mean values of BRATIO and TPI for park trees after controlling for tree age. Study results suggest that tree performance evaluated with size metrics (dbh and CPA) versus composite metrics (BRATIO and TPI) may prioritize faster growth over sustained longer-term growth.